2017
DOI: 10.1111/mmi.13721
|View full text |Cite
|
Sign up to set email alerts
|

A novel streptococcal cell–cell communication peptide promotes pneumococcal virulence and biofilm formation

Abstract: Streptococcus pneumoniae (pneumococcus) is a major human pathogen. It is a common colonizer of the human respiratory track, where it utilizes cell-cell communication systems to coordinate population-level behaviors. We reasoned that secreted peptides that are highly expressed during infection are pivotal for virulence. Thus, we used in silico pattern searches to define a pneumococcal secretome, and analyzed the transcriptome of the clinically important PMEN1 lineage to identify which peptide-encoding genes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 95 publications
(140 reference statements)
1
64
0
Order By: Relevance
“…We propose that VP1 serves as a marker for 48 colonization and a target for drug design. We have previously shown that vp1 plays a role in biofilm development (7). Thus, we 135 investigated whether vp1 influences attachment to epithelial cells, an early step in biofilm 136 formation.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…We propose that VP1 serves as a marker for 48 colonization and a target for drug design. We have previously shown that vp1 plays a role in biofilm development (7). Thus, we 135 investigated whether vp1 influences attachment to epithelial cells, an early step in biofilm 136 formation.…”
mentioning
confidence: 98%
“…60 61 Pneumococcus secretes many small peptides, which influence colonization, virulence, 62 and adaptation via effects on competence, intra-species competition, and biofilm development 63 (6-18). The Virulence Peptide 1 (VP1) is a member of a family of peptides with a conserved N-64 terminal sequence characterized by a double glycine motif, which directs its export into the 65 extracellular milieu via ABC transporters (7,19). The vp1 gene is widely distributed across 66 pneumococcal strains, as well as encoded in related streptococcal species.…”
mentioning
confidence: 99%
See 3 more Smart Citations